Strategi Efektif Dalam Penyusunan Undang-Undang: Mengupas Teknik Dan Tantangan Pembentukan Hukum Di Indonesia - Zulfa Asdiqi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study examines the challenges and effective strategies in the law-making process in Indonesia to produce clear, consistent, and easily understandable regulations. The legislative process in Indonesia often faces various issues such as a lack of harmonization between regulations, limited public participation, and political influence in the formulation of laws. This research also compares the law-making practices in Indonesia with countries that have higher rule of law indexes, such as Denmark, Finland, and Singapore. The study found that wider public involvement, transparency in the legislative process, and comprehensive regulatory impact assessments can improve the quality of laws in Indonesia. Therefore, this study recommends strengthening public consultations, conducting more thorough impact assessments, and enhancing the capacity of law drafters as key measures to improve legislative quality in Indonesia.